Discovery of benzo[d]oxazol-2(3H)-one derivatives as a new class of TNIK inhibitors for the treatment of colorectal cancer. (1st July 2022) - Luo, Xinling; Yang, Ruicheng; Li, Yueshan; Zhang, Liting; Yang, Shengyong; Li, Linli
Graphical abstract: Abstract: Colorectal cancer (CRC) is one of the most commonly diagnosed cancer types and Traf2- and Nck-interacting kinase (TNIK) has been thought as a potential target for CRC treatment. Herein we report the discovery and structure–activity relationship (SAR) of benzo[ d ]oxazol-2(3 H )-one derivatives as a new class of TNIK inhibitors. The most potent compound 8 g showed an IC50 value of 0.050 μM against TNIK. It effectively suppressed proliferation and migration of colorectal cancer cells. Western blot analysis indicated that 8 g could inhibit aberrant transcription activation of Wnt signaling. Collectively, this study provides a potential lead compound for subsequent drug discovery targeting TNIK.